(untitled) (Research, Society and Development, 2022)
The present study aimed to present what the national scientific literature produced on the humanization of care in the context of Intensive Care Units. An integrative literature review of articles published in Brazil between the years 2011 to 2021 was carried out. The analysis was carried out with the aid of an instrument constructed by the author. As a result, among 202 texts found, only six addressed the content of humanization in the context of Intensive Care Units. There were no publications in the North, Midwest, and South regions. Professionals, patients, and companions/family members were the main target audience in the surveys and expressed the conditions of care in critical environments. For professionals, the main difficulties are related to human and structural resources, but they still strive to develop humanization in care. Patients and users recognize such dedication, but suggest improvements in communication, including with the patient and family. In view of the above, we understand that professionals must be aware of the practice of more human behaviors and attitudes, with the involvement of managers and patients in the organization of the work process, complying with the precepts of the National Humanization Policy and providing opportunities for planning more directed to the difficulties that permeate daily life in Intensive Care Units, always with management support.